Fios ortodônticos superelásticos e sua aplicabilidade na clínica ortodôntica: revisão da literatura - Jacob, Vanessa Peret [UNESP]; Oliveira, Derly Tescaro Narcizo de [UNESP]; Bigliazzi, Renato [UNESP]; Bertoz, André Pinheiro de Magalhães [UNESP] (My University, 2010)
During clinical routine, the orthodontist uses several materials, which include metallic alloys in the form of metallic wires. However, it is necessary that the professional has some knowledge of the properties of those wires. Different types of wires are commercially available: stainless steel wires, chrome-cobalt wires, nickel-titanium wires and beta-titanium wires. Among the nickel-titanium wires, there are three subdivisions: a conventional alloy and two superelastic alloys. The superelasticity, associated to the effect of form memory, is a property used in orthodontics to initiate the dental movement in the first phase of the orthodontic treatment. This property is considered to be biologically compatible with the effective dental movement. These wires are available at the market in different transformation temperatures, and they offer the best adaptation in the groove of the bracket, simplicity and a faster treatment. However, they present little formability, and they don’t accept solder. They are also more onerous than other wires. Moreover, the low rigidity of these wires doesn’t allow them to be used for the retraction of the anterior teeth or closing of spaces. Therefore, the coherent use of superelastic orthodontic wires is recommended, accompanied by a detailed diagnosis and planning, so the result will be an efficient orthodontic correction, accomplished in a shorter period of time.

Na rotina clínica diária, o ortodontista usa diversos materiais, que incluem ligas metálicas na forma de fios metálicos. Entretanto, para que o profissional exerça uma Ortodontia de excelência é necessário que ele tenha conhecimento das propriedades desses fios. Existem diferentes tipos de fios no mercado: fios de aço inoxidável, fios de cromo-cobalto, fios de níquel-titânio e fios de beta-titânio. Entre os fios feitos de liga de níquel-titânio, existem três subdivisões: uma liga convencional e duas ligas superelásticas. A superelasticidade, associada ao efeito memória de forma, é uma propriedade usada em ortodontia para iniciar o movimento dentário na primeira fase do tratamento ortodôntico. Essa propriedade é considerada biologicamente compatível com o movimento dentário efetivo. Esses fios apresentam-se no mercado em diferentes temperaturas de transformação, oferecem a melhor adaptação na ranhura do braquete, proporcionando maior simplicidade e rapidez ao tratamento. Entretanto, apresentam pouca formabilidade, e não aceitam solda. Também são mais onerosos que outros fios. Além disso, a baixa rigidez desses fios não permite que sejam utilizados para a retração dos dentes anteriores ou fechamento de espa- ços. Portanto, recomenda-se o uso coerente dos fios ortodônticos superelásticos, acompanhado de um ótimo diagnóstico e planejamento, para que o resultado seja uma correção ortodôntica mais eficiente e realizada em menor período de tempo.
Superelastic orthodontic wires and its application in clinical orthodontics: literature review
Keywords: Orthodontic wires; Superelasticity; Biomechanics; Fios ortodônticos; Superelasticidade; Biomecânica